CONDITIONS OF ORGANIZING INTERACTION BETWEEN THE TEACHING STAFF AND THE FAMILY AND MODELS OF INTERACTION MANAGEMENT (EDUCATION IN THE 21ST CENTURY, 2025)
Over the past decades, due to changes in social and economic conditions in society, as well as the introduction of new technologies into everyday life, the psychology and behavior of each member of society have changed. New problems arise between children and parents, children and school, school and parents. In this regard, the role of cooperation between school and society increases. The modern school is faced with new forms and methods of cooperation and interaction, which are difficult for both teachers and parents to perceive. As a result, it becomes obvious that we are dealing with new conditions for organizing interaction between the family and the teaching staff, parents and children.In the modern history of pedagogy, a number of well-known teachers, psychologists, and sociologists addressed this problem, put forward approaches, offered programs and models that were of particular importance in organizing interaction between the teaching staff and the family. We often referred to their approaches and ideas in the article. Attention was paid to a number of models of managing interaction between parents and children. The behavior of teachers, parents and children, the specifics of support provided to a modern family, and the content of pedagogical support are commented on.The work examines the forms of communication between the teaching staff and parents, their effectiveness and role as a modern process.In the article, we identified five determinants of parent-child interaction that are of fundamental importance in the formation and development of the moral, psychological, socio-cultural atmosphere of a modern family.Approaches to organizing school-parent cooperation and, through it, interaction between parents and children are defined, as a result of which the nature, principles and individual components of cooperation change, and ultimately the goals, content, forms and technologies of interaction change.
Keywords: cooperation; interaction; cooperation condition; management model; atmosphere of mutual trust; pedagogical culture; behavioral psychology; ego state; ethnopedagogical approach